Human Resource Functions and Job Performance in Public Institutions in Kamwenge District Local Government - Musika, Japheth; Atwiine, Johnson; Kembabazi, Juliet (East African Journal of Arts and Social Sciences, 2023)
The study aimed at investigating the relationship between Human Resource function and employee job performance in Kamwengye district. Particularly, to establish the influence of supervision on job performance in Kamwenge District. The research design was cross sectional research design. The study was informed by 69 respondents who participated in the study and these were selected using simple random sampling and purposive sampling whereby data was conducted using questionnaire survey and interview guide. The data was analysed using descriptive, inferential statistics, and content analysis. The study found and concluded that supervision has a strong statistically significant association with job performance